2016
DOI: 10.1002/joc.4923
|View full text |Cite
|
Sign up to set email alerts
|

Teleconnection patterns impacting on the summer consecutive extreme rainfall in Central‐Eastern China

Abstract: Consecutive extreme rainfall (CER) events can cause enormous damage to human society and the environment in eastern China. This study analyses persistent atmospheric circulation patterns related to dominant CER modes over Central‐Eastern China. Results reveal that the two leading modes together explain 30% of the total CER variance. The circulation patterns related to the first CER mode manifest a barotropic Eurasian (EU) pattern teleconnection 4 days before the CER events occur in the southern Yangtze River. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 60 publications
(71 reference statements)
0
11
0
Order By: Relevance
“…Prolonged weather extremes result dynamically from long‐lived atmospheric flow patterns, whose duration spans from days to weeks (Higgins and Mo, ; Stadtherr et al., ; Mann et al., ; Kornhuber et al., ). Recurrent atmospheric teleconnections composed of adjacent cyclones/anticyclones are deemed one major source for the persistence of weather extremes (Chen and Zhai, ; Lü et al ., ; Steptoe et al., ). Monthly‐/seasonal‐scale indices of atmospheric teleconnections used to be employed in explaining, monitoring and predicting climate anomalies at interannual to inter‐decadal time‐scales (Wallace and Gutzler, ; Nitta and Hu, ; Kubota et al., ).…”
Section: Introductionmentioning
confidence: 97%
“…Prolonged weather extremes result dynamically from long‐lived atmospheric flow patterns, whose duration spans from days to weeks (Higgins and Mo, ; Stadtherr et al., ; Mann et al., ; Kornhuber et al., ). Recurrent atmospheric teleconnections composed of adjacent cyclones/anticyclones are deemed one major source for the persistence of weather extremes (Chen and Zhai, ; Lü et al ., ; Steptoe et al., ). Monthly‐/seasonal‐scale indices of atmospheric teleconnections used to be employed in explaining, monitoring and predicting climate anomalies at interannual to inter‐decadal time‐scales (Wallace and Gutzler, ; Nitta and Hu, ; Kubota et al., ).…”
Section: Introductionmentioning
confidence: 97%
“…Their results suggest that the anomalous southerlies over the northwest flank of the western Pacific subtropical high are unfavourable for the convergence of warm moist air from the south and cold dry air from the north. Recently, Lü et al () suggested that dipolar SST anomalies in the northeastern Atlantic are related to consecutive extreme rainfall events in central eastern China through generating an EU‐like teleconnection. The location of SST anomalies in the northeastern Atlantic in their study is close to the quasi‐north–south SST anomaly pattern revealed in the present study (Figure b).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Some studies indicated that the coupled relationship between the North Atlantic tripole SST and North Atlantic Oscillation could lead to a strong EASM via modulating the blocking highs in the Ural Mountain and Okhotsk Sea (Wu et al, 2009;Wu et al, 2011;Zuo et al, 2012;. Lü et al (2017) revealed that a dipolar SST anomaly in the northeastern Atlantic is closely related to consecutive extreme rainfall events over central eastern China through the propagation of Rossby waves.…”
Section: Low-latitude Highlands (Llh) Are the Areas Located Between 30mentioning
confidence: 99%
See 2 more Smart Citations